Potential Advances of Adjunctive Hyperbaric Oxygen Therapy in Infective Endocarditis - Lerche, Christian Johann; Schwartz, Franziska; Pries-Heje, Mia Marie; Fosbøl, Emil Loldrup; Iversen, Kasper; Jensen, Peter Østrup; Høiby, Niels; Hyldegaard, Ole; Bundgaard, Henning; Moser, Claus (Frontiers in Cellular and Infection Microbiology, 2022)
Patients with infective endocarditis (IE) form a heterogeneous group by age, co-morbidities and severity ranging from stable patients to patients with life-threatening complications with need for intensive care. A large proportion need surgical intervention. In-hospital mortality is 15-20%. The concept of using hyperbaric oxygen therapy (HBOT) in other severe bacterial infections has been used for many decades supported by various preclinical and clinical studies. However, the availability and capacity of HBOT may be limited for clinical practice and we still lack well-designed studies documenting clinical efficacy. In the present review we highlight the potential beneficial aspects of adjunctive HBOT in patients with IE. Based on the pathogenesis and pathophysiological conditions of IE, we here summarize some of the important mechanisms and effects by HBOT in relation to infection and inflammation in general. In details, we elaborate on the aspects and impact of HBOT in relation to the host response, tissue hypoxia, biofilm, antibiotics and pathogens. Two preclinical (animal) studies have shown beneficial effect of HBOT in IE, but so far, no clinical study has evaluated the feasibility of HBOT in IE. New therapeutic options in IE are much needed and adjunctive HBOT might be a therapeutic option in certain IE patients to decrease morbidity and mortality and improve the long-term outcome of this severe disease.